Analisis Modal Kerja Terhadap Profitabilitas PT. Unilever Indonesia Tbk Yang Terdaftar Pada BEI (2019-2023) - Nanda Satria, Gusti (Journal Of Accounting and Business, 2025)
This study aims to analyze the effect of working capital on the profitability of PT Unilever Indonesia Tbk listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Working capital is measured using the Current Ratio (CR), Quick Ratio (QR), and Cash Ratio (CaR), while profitability is measured using the Operating Profit Margin (OPM). Effective working capital management is essential to maintaining the company's liquidity, supporting operational activities, and improving profitability. This research employs a quantitative descriptive approach using secondary data obtained from the annual financial statements of PT Unilever Indonesia Tbk published by the Indonesia Stock Exchange and the company's official website. The data were analyzed using descriptive analysis to examine changes in working capital and profitability over the five-year observation period. The results indicate that working capital experienced fluctuating changes, as reflected in the Current Ratio, Quick Ratio, and Cash Ratio. These fluctuations affected the company's profitability, particularly its Operating Profit Margin, indicating that the effectiveness of working capital management plays an important role in generating operating profit. This study provides empirical evidence that changes in working capital components influence the company's financial performance and can serve as a reference for management in optimizing working capital policies to improve profitability.